Islamic sufi networks in the western Indian Ocean (c. 1880-1940) : ripples of reform - Bang, Anne K. (Islam in Africa, 2014)
In the period c. 1880-1940, organized Sufism spread rapidly in the western Indian Ocean. New communities turned to Islam, and Muslim communities turned to new texts, practices and religious leaders. On the East African coast, the orders were both a vehicle for conversion to Islam and for reform of Islamic practice. The impact of Sufism on local communities is here traced geographically as a ripple reaching beyond the Swahili cultural zone southwards to Mozambique, Madagascar and Cape Town. Through an investigation of the texts, ritual practices and scholarly networks that went alongside Sufi expansion, this book places religious change in the western Indian Ocean within the wider framework of Islamic reform.